2022
DOI: 10.20473/j.djmkg.v55.i1.p56-61
|View full text |Cite
|
Sign up to set email alerts
|

Exercise as a method to reduce the risk of oral cancer: A narrative review

Abstract: Background: Cancer is a major cause of death worldwide. One of the most common forms of cancer is oral cancer, which can occur due to exposure to carcinogenic factors, such as tobacco cigarettes, alcohol, betel-nut chewing, ultraviolet rays or human papillomavirus infection. Physical exercise is known to have many benefits and can contribute to reducing the risk of cancer, minimising the side-effects of treatment and increasing the curative effect of cancer treatment. Purpose: This study aimed to explain the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Caspase-3 activates CAD (Caspase-Activated DNase) endonuclease and via developing apoptotic bodies, the creation of the transformed epithelial cells of the oral squamous cell is prevented [ 19 ]. In conclusion, moderate-intensity exercise in mice led to an increased Caspase-3, and the Bax/Bcl-2 ratio, which induces apoptosis [ 20 , 21 ]. Irmawati et al suggested that physical activity reduces the risk of oral cancer occurrence by diminishing the formation of transformed cells and decreasing the expression of the p53 mutant [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caspase-3 activates CAD (Caspase-Activated DNase) endonuclease and via developing apoptotic bodies, the creation of the transformed epithelial cells of the oral squamous cell is prevented [ 19 ]. In conclusion, moderate-intensity exercise in mice led to an increased Caspase-3, and the Bax/Bcl-2 ratio, which induces apoptosis [ 20 , 21 ]. Irmawati et al suggested that physical activity reduces the risk of oral cancer occurrence by diminishing the formation of transformed cells and decreasing the expression of the p53 mutant [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, moderate-intensity exercise in mice led to an increased Caspase-3, and the Bax/Bcl-2 ratio, which induces apoptosis [20,21]. Irmawati et al suggested that physical activity reduces the risk of oral cancer occurrence by diminishing the formation of transformed cells and decreasing the expression of the p53 mutant [21]. In a study by Moore et al in 2016 based on 12 prospective cohorts, a total of 1.44 million individuals with self-reported physical activity were recruited.…”
Section: Plos Onementioning
confidence: 99%
“…Continuous exercise is carried out without any rest breaks, while interval exercise is carried out according to the duration of time intensity but with the presence of rest times. 12 In this study, moderate-intensity exercise is used. The chosen moderate-intensity exercise is swimming because it has minimal injury, moves all limbs, and the entire body weight is held by water.…”
Section: Introductionmentioning
confidence: 99%